2009
DOI: 10.1080/09638180902863803
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Interactive Control Systems under Different Innovation Management Modes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
1
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(158 citation statements)
references
References 87 publications
7
131
1
19
Order By: Relevance
“…Esta investigação explora a dimensão uso do SCG, com base no modelo de alavancas de controle de Simons (1990Simons ( , 1991Simons ( , 1995, que tem sido largamente utilizado em pesquisas da área de controle gerencial (Abernethy & Brownell, 1999;Bisbe & Malagueño, 2009;Bisbe & Otley, 2004;Harlez & Malagueño, in press;Sánchez, López-Valeiras, Rodríguez-González, & Feliu, 2013;Widener, 2007). Para Simons (1995), uma estrutura específica de quadro alavancas proporciona o controle estratégico das organizações, e a forma como os gestores utilizam esses sistemas é fundamental à empresa.…”
Section: Sistema De Controle Gerencialunclassified
See 1 more Smart Citation
“…Esta investigação explora a dimensão uso do SCG, com base no modelo de alavancas de controle de Simons (1990Simons ( , 1991Simons ( , 1995, que tem sido largamente utilizado em pesquisas da área de controle gerencial (Abernethy & Brownell, 1999;Bisbe & Malagueño, 2009;Bisbe & Otley, 2004;Harlez & Malagueño, in press;Sánchez, López-Valeiras, Rodríguez-González, & Feliu, 2013;Widener, 2007). Para Simons (1995), uma estrutura específica de quadro alavancas proporciona o controle estratégico das organizações, e a forma como os gestores utilizam esses sistemas é fundamental à empresa.…”
Section: Sistema De Controle Gerencialunclassified
“…Ainda que pesquisas sobre controle gerencial e liderança (Abernethy et al, 2010;Jansen, 2011), inovação e liderança (Alsalami, Behery, & Abdullah, 2014;García-Morales, Jiménez-Barrionuevo, & Gutiérrez-Gutiérrez, 2012;Gumusluoglu & Ilsev, 2009) e controle gerencial e inovação (Arjaliès & Mundy, 2013;Bisbe & Malagueño, 2009;Chong & Mahama, 2014) tenham se intensificado nos últimos anos, o tratamento conjunto desses três constructos (liderança, controle gerencial e inovação) ainda representa uma lacuna no ambiente de pesquisa científica. Desse modo, este estudo proporciona contribuições relevantes, no sentido de integrar dois constructos (estilo de liderança e controle gerencial) cujo efeito na inovação já foi empiricamente comprovado, porém de forma não integrada.…”
unclassified
“…Regarding the measurement of the variables, a sophisticated management information system was measured based on the scale developed by previous studies [36,40], where the design of management information systems was conceptualized in terms of four information characteristics, such as (1) scope; (2) timeliness; (3) aggregation and (4) integration. General service directors were asked to indicate in a five point Likert scale from 1 (very low) to 5 (very high) the extent to which their hospital's management information system provides each of those four dimensions identified.…”
Section: Methodsmentioning
confidence: 99%
“…In this line, several researchers have argued that an interactive use of management information systems facilitate the adoption of innovative ideas and solutions through the provision of encouragement for triggering of new initiatives, processes and activities [35,39]. It has also been argued that an interactive (diagnostic) style of using management information systems contributes positively (negatively) to the quality management and organizational learning [14,40]. Therefore, I formulated the following hypotheses: Hypothesis 1 (H1).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…They concluded that management control systems influence and are influenced by strategy: the mechanisms of management control used by interactive mode facilitate strategic change and, on its turn, the management control mechanisms adapt to the strategic changes that take place. Bisbe and Malagueno (2009), analyzing a sample of medium-sized Spanish companies, conclude that the specific choice of an individual MCS for interactive use is related to the type of innovation mode that the company is dedicated to. In this sense, the authors found evidence that companies dedicated to simple and isolated forms of innovation and companies looking to create a rich portfolio of innovation usually tend to select PMS for interactive use.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%